VD_FINDINFO Jug / 2020 / 47 vom 25. September 2019 - VD Tribunal cantonal (2019)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, RÉVOCATION DU SURSIS, PEINE D'ENSEMBLE, DÉTENTION ILLICITE | 46 CP, 47 CP, 49 al. 1 CP, 10 CPP (CH), 431 al. 1 CPP